A comparative analysis of two food security and nutrition policies in Yemen between 2018 and 2023: agricultural livelihoods and multisectoral nutrition plan - Alessandro Demurtas; Audrey Occansey Agbeko (Global Security: Health, Science and Policy)
This article compares two food security and nutrition policies in Yemen, analysing their effectiveness and their ideational and institutional alignment with the United Nations’ Human Security approach. The two policies are Yemen plan of action 2018–2020: Strengthening Resilient Agricultural Livelihoods and Yemen Multisectoral Nutrition Action Plan 2020–2023. The qualitative comparison and analysis is based on national and international primary open access sources published between 2019 and 2023. The most relevant findings are classified using a triple analytical prism. First, despite some relevant progress, the ideational factors of the two case studies are partially aligned with the Human Security approach, especially in reference to Sustainable Development Goals coverage. Second, regarding the institutional dimension of the policies, despite the fulfilment of most normative and participation requirements, a problem that still remains is non-compliance with international standards in three areas: national regulations on labour conditions, climate-change considerations in infrastructure construction, and participation of civil society. Third, regarding policy effectiveness, both policies have some limitations related to lack of funding and instability in Yemen exacerbated by violence and COVID-19.